Legislative Incompetence Resulting from Poor Recruitment and It’s Implications for National Economic Policy - Eprinalia A; Laila Refiana Said; A Suriansyah; Patardo Haholongan Nainggolan; Indra Jaya Saputra (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the causal relationship between the failure of political party recruitment design and the emergence of legislative incompetence and its implications for the quality of national economic policy. The background of this study is based on the phenomenon of low capacity of legislative members in carrying out legislative, budgeting, and oversight functions, which directly impacts the country's economic performance. The method used is an explanatory sequential mixed-methods approach with an institutional analysis and economic policy evaluation approach. Quantitative data were obtained from the profiles of members of the House of Representatives (DPR) for the 2019–2024 period and macroeconomic indicators, while qualitative data came from in-depth interviews and analysis of policy documents. The results show that weak regulations in political recruitment, particularly the absence of competency standards and merit-based selection mechanisms, have resulted in the dominance of legislators with low economic capacity. This condition triggers distortions in the legislative process, budgeting, and oversight of economic policy, characterized by budget misallocation, inconsistent policies, and low quality economic regulations. Further implications are seen in increasing fiscal inefficiency, a weakening investment climate, and hampered inclusive economic growth. This study concludes that reform of the political recruitment system is a fundamental prerequisite for improving the quality of national economic policy and promoting sustainable development.